Distinguishing between organic and inorganic phosphorus in hydroxyapatite by elemental analysis - Daniels, Yasmine (Microchem J, 2013)
A method is developed to determine the amount of organic and inorganic phosphorus in an inorganic polymer (hydroxyapatite (HAP)) modified with an organic phosphorus – containing complexant. The simplicity and precision of the vanadate method has made it useful for measuring the total phosphorus content in phosphorus – containing organic polymers that are first digested in concentrated sulfuric acid. However, it can be important to quantify the organic and inorganic phosphorus capacities in modified (hybrid) polymers and this method does not distinguish between the two. In the current report, HAP was modified with 1-hydroxyethane-1,1-diphosphonic acid (HEDP) and a method developed to give the respective phosphorus capacities. HAP was contacted with HEDP for 17 h, 28 h, 56 h, 84 h, 112 h, and 140 h. By combining results from the sulfuric acid digestion of the modified polymer with those from a separate digestion in HCl, it was determined that there was a monotonic increase in the organic phosphorus capacity from 0.04 to 2.44 mmol / g, and a decrease in the inorganic phosphorus capacity from 4.68 to 2.54 mmol / g.